2021
DOI: 10.7759/cureus.12663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Characteristics Including Comorbidities and Their Outcomes Among Patients Hospitalized With COVID-19 in Four Tertiary Care Hospitals Across Lahore

Abstract: Background The first case of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was diagnosed in Wuhan, China, in 2019. By the first half of 2020, coronavirus disease 2019 (COVID-19) turned into a global pandemic. Objectives The aim of this study is to describe the clinical and demographic characteristics including comorbidities and their outcomes among patients hospitalized with COVID-19 in four tertiary care hospitals across Lahore . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In contrast, Zhou et al reported high mortality and ICU admissions (28.3% and 26%, respectively) [28]. Surprisingly, a local study from Lahore reported 8.3% mortality; however, 30.7% of their patients required ICU care [29]. The differences in our study and one from Lahore may be explained by the availability of intensive care beds, as we were working in a relatively small private hospital as opposed to the pooling of data from four large public and private sector hospitals in Lahore.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Zhou et al reported high mortality and ICU admissions (28.3% and 26%, respectively) [28]. Surprisingly, a local study from Lahore reported 8.3% mortality; however, 30.7% of their patients required ICU care [29]. The differences in our study and one from Lahore may be explained by the availability of intensive care beds, as we were working in a relatively small private hospital as opposed to the pooling of data from four large public and private sector hospitals in Lahore.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies provide limited evidence on the clinical characteristics of SARS-CoV-2 infection in Pakistan [31][32][33][34][35][36][37][38][39][40][41][42][43]. These studies had several limitations, including a small sample size or data collection at a single diagnostic center.…”
Section: Resultsmentioning
confidence: 99%
“…95660 patients (33.3%) were hospitalized in ICUs (Supplementary Digital Material 1: Supplementary Table 1). The median age of the study population was 64 years (widest range 23-98 73 ), with the lowest mean age of 54 years reported by Khan Chachar and coworkers 36 and the highest (median 72 -IQR, 60-82) reported by Amit et al 57 . Distribution of comorbidities is reported in Supplementary Digital Material 1: Supplementary Figure 1.…”
Section: Copyright© Edizioni Minerva Medicamentioning
confidence: 77%
“…PaCO2 at admission was available in nine studies 19,24,27,[29][30][31]33,35,42 (17%), and median PaCO2 values ranged from 33 mmHg 19,33 to 42 mmHg 30 (Supplementary Digital Material 1: Supplementary Table 2). Respiratory rate at admission was reported in 21 studies 19,23,25,27,28,30,32,33,35,36,39,40,45,47,[56][57][58]60,62,70 (40.4%), and generally ranged from 18-20 breaths/min 28,45,56,60 to 27-28 breaths/min 25,35 .…”
Section: Gas Exchange At Admissionmentioning
confidence: 99%
See 1 more Smart Citation